Coaching Parents of Children with Sensory Integration Difficulties: A Scoping Review. (17th June 2021) - Allen, Susan; Knott, Fiona J.; Branson, Amanda; Lane, Shelly J.
Abstract : Aim . To review current evidence regarding the effectiveness of occupational therapy coaching interventions for parents of children with sensory integration difficulties, delivered to individuals or groups of parents. Method . A historical scoping review was completed of empirical research records to summarize what is known and how this information can guide future research. The process was guided by PRISMA guidelines. Inclusion criteria were English language and peer-reviewed empirical studies of parent coaching intervention for children with sensory processing or sensory integration difficulties. Five databases were searched. Papers were critically reviewed using McMaster's guidelines. Results . Four studies met the search criteria. Three studies took a direct coaching approach with individual parents or families. The fourth study took a mixed educational/coaching approach with groups of parents and teachers. Conclusion . There is some evidence to conclude that occupational therapists can deliver individual parent-focused coaching interventions which impact positively on individual child goals, parental stress, and sense of competence. Group intervention can lead to caregivers' improved perceived and actual knowledge of sensory integration, as well as a sense of self-efficacy in dealing with sensory-related child behaviors. Current evidence is limited. Suggestions for future research are offered.